2008
DOI: 10.1093/eurpub/ckn066
|View full text |Cite
|
Sign up to set email alerts
|

Study of the impact of laws regulating tobacco consumption on the prevalence of passive smoking in Spain

Abstract: Implementation of the smoking ban resulted in a significant decrease in exposure to ETS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 11 publications
1
26
1
3
Order By: Relevance
“…According to a previous study [10], the overall prevalence of exposure to SHS in 2005 was 49.5%. Table 2 and figure 2 show the changes observed in overall exposure to SHS in 2007 and 2011.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a previous study [10], the overall prevalence of exposure to SHS in 2005 was 49.5%. Table 2 and figure 2 show the changes observed in overall exposure to SHS in 2007 and 2011.…”
Section: Resultsmentioning
confidence: 99%
“…In the wake of the introduction of this law, several studies found that the reduction in exposure to SHS was not as marked as expected and, of course, that no reduction was noted at entertainment venues [10,11,12]. In a previous study that we undertook to evaluate the impact of this law, we found that the overall prevalence of exposure to environmental tobacco smoke decreased from 49.5% in 2005 to 37.9% in 2007, with the greatest reduction in this prevalence occurring in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This legislation, aimed to protect the health of non-smokers, did not meet expectations. Some studies showed major reductions in the exposure to SHS at the workplace, but no significant changes were observed at home or in leisure spaces (Galán et al, 2007;Jiménez-Ruiz et al, 2008). As a result, the law was amended five years later on January 2 2011, establishing a more severe anti-smoking regime (Law 42/2010, of December 30) and imposing a complete ban on smoking in enclosed public places, on public transport, and in the workplace.…”
mentioning
confidence: 99%
“…For example, while a 2004 study indicated that more than 75% of smokers in Taiwan smoked in the workplace (Wen et al 2004), the workplace smoking rate in Taiwan in 2008 was reported as 20% (Chao et al 2009). Following initiation of a 2006 law partially restricting workplace smoking in Spain, workplace exposure decreased from 25.8 to 11% (Jiménez-Ruiz et al 2008). However, there was no significant change in exposure to smoking in Spanish workplace venues that continued to permit smoking (e.g., discotheques and pubs) (Nebot et al 2009).…”
Section: Introductionmentioning
confidence: 99%